Pengaruh Opinion Shopping, Likuiditas dan Ukuran Perusahaan terhadap Opini Audit Going Concern: Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar Di Bursa Efek Indonesia - Yunita, Ririn; Halmawati, Halmawati (Universitas Negeri Padang, 2024)
This research aims to provide empirical evidence regarding the influence of opinion shopping, liquidity and company size on going concern audit opinion. Going Concern shows the company is able to maintain its business in the long term. If there is doubt about the company's survival, the auditor will issue a going concern audit opinion. The issuance of a going concern audit opinion will influence investor decisions. The dependent variable in this research is going concern audit opinion. The independent variables are opinion shopping, liquidity, and company size. The research design is a quantitative method. The companies studied are property and real estate companies listed on the Indonesia Stock Exchange within the 5 year period 2018-2022. The sample was selected using the purposive sampling method. Data analysis was carried out using logistic regression. The results of the analysis show that opinion shopping has a positive and significant effect on going concern audit opinion, liquidity has no significant effect on going concern audit opinion and company size has a positive and significant effect on going concern audit opinion.